Thyroid Disorders Change the Pattern of Response of Angiotensinase Activities in the Hypothalamus-Pituitary-Adrenal Axis of Male Rats - Segarra, Ana B.; Prieto, Isabel; Martínez-Cañamero, Magdalena; de Gasparo, Marc; Luna, Juan de Dios; Ramírez-Sánchez, Manuel (Frontiers in Endocrinology, 2018)
Thyroid disorders affect the hypothalamic-pituitary-adrenal (HPA) axis with important consequences on the cardiovascular function in which the renin-angiotensin system (RAS) plays a major role. Hypo and hyperthyroidism influence the classic main components of the RAS. However, the behavior of other RAS elements like Ang III, Ang 2-10, Ang IV or AT4, regulated by angiotensinase enzymes such as alanyl- (AlaAP), cystinyl- (CysAP), glutamyl- (GluAP) or aspartyl-aminopeptidase (AspAP), has not yet been described. In order to obtain a comprehensive view on the RAS response in the HPA axis of animals with thyroid disorders, these enzyme activities were simultaneously analyzed fluorometrically, using arylamide derivatives as substrates in hypothalamus, anterior and posterior pituitary, adrenals and plasma of eu- (EU)- hypo- (HYPO) and hyperthyroid rats (HYPER), and their intra- and inter-tissue interactions were evaluated. The response depended on the type of enzyme studied, its location and the thyroid status. Anterior pituitary, adrenals and plasma were mainly affected by the thyroid disorders. In the anterior pituitary, GluAP and AspAP increased in HYPO. In adrenals, AlaAP and CysAP decreased in HYPO whereas GluAP and AspAP decreased in HYPER. In plasma, while AlaAP increased in HYPO and HYPER, CysAP and GluAP decreased only in HYPER. In comparison with EU, intra-tissue correlations increased in HYPO but inter-tissue correlations decreased in both thyroid disorders, mainly in HYPO. Thyroid disorders also produced a disruption in the pattern of inter-tissue interactions observed in EU. These results suggest that thyroid hormone levels hit components of the RAS and may influence on the paracrine and endocrine cross talk between cells.